1997
DOI: 10.1128/aac.41.11.2456
|View full text |Cite
|
Sign up to set email alerts
|

Ribosylative inactivation of rifampin by Mycobacterium smegmatis is a principal contributor to its low susceptibility to this antibiotic

Abstract: Mycobacterium smegmatis inactivates rifampin by ribosylating this antibiotic. The gene responsible for this ability was cloned and was shown to confer low-level resistance to this antibiotic (MIC increase, about 12-fold) in related organisms. A 600-bp subclone responsible for ribosylating activity and resistance carried an open reading frame of 429 bp. Targeted disruption of the gene in M. smegmatis resulted in mutants with much increased susceptibility to rifampin (MICs of 1.5 instead of 20 microg/ml) as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 34 publications
6
54
0
Order By: Relevance
“…Serial dilution plate counts determined this to correspond to 3.8e8 CFU/mL. The Minimal Inhibitory Concentration (MIC) was reported in the literature26 to be 20 μg/mL and this was confirmed by visual MIC assays. Various multiples of this concentration, including 1/4X, 1/2X, 1X, 2X and 5X this MIC were tested for growth effects through growth curves (1X and 2X in Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…Serial dilution plate counts determined this to correspond to 3.8e8 CFU/mL. The Minimal Inhibitory Concentration (MIC) was reported in the literature26 to be 20 μg/mL and this was confirmed by visual MIC assays. Various multiples of this concentration, including 1/4X, 1/2X, 1X, 2X and 5X this MIC were tested for growth effects through growth curves (1X and 2X in Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…2). We are investigating whether the difference in their antibacterial activities is due to differences in intrabacterial pharmacokinetic properties of the rifamycin derivatives, i.e., differences in bacterial drug uptake, efflux, or metabolism (45, 48, 49). Understanding the mechanistic basis of the activity differences may open new avenues to inform medicinal chemistry efforts and discover more potent rifamycins for the treatment of mycobacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that M. smegmatis is naturally resistant to RIF even though no mutations have been characterized in the RIF resistance-determining region of the rpoB gene [1], [23]. Although some evidence has shown that RIF inactivation via ribosylation may be a principal mechanism of RIF resistance in M. smegmatis , this mechanism cannot solely account for its high level of RIF resistance [1], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although some evidence has shown that RIF inactivation via ribosylation may be a principal mechanism of RIF resistance in M. smegmatis , this mechanism cannot solely account for its high level of RIF resistance [1], [23]. It has been demonstrated that porin MspA plays an important role in the influx of quaternary ammonium compounds and antibiotics in M. smegmatis [24]; however, the efficacy of rifampicin against M. smegmatis is not strongly affected by the absence of porin [25], implying that other unknown mechanisms are involved in the regulation of rifampicin resistance in M. smegmatis .…”
Section: Discussionmentioning
confidence: 99%